Analisis Efektivitas Biaya Amitriptilin dan Gabapentin pada Pasien Stroke dengan Nyeri Neuropati di Instalasi Rawat Inap RSUD Provinsi NTB Tahun 2017 - Febhi Pratiwi; Candra Eka Puspitasari; GAP Sri Erwinayanti; Royani Widiyastuti (Jurnal Sains dan Kesehatan, 2020)
Neuropathic pain which is suffered by stroke patients is a pain that occurred because of the damage of the somato sensory system. The first-line therapy of neuropathic pain can be done by using amitriptyline and gabapentin. Both amitriptyline and gabapentin have significant cost-effectiveness differences. This research aims to investigate the cost effectiveness of both amitriptyline and gabapentin through stroke patients who suffered neuropathic pain. The techniques of data collection applied to a total sampling which are 17 samples were collected. The data were retrospective by the year of 2017, meanwhile, the research was conducted from April to July 2019. Clinical evaluation of neuropathic pain is conducted by applying the Wong Baker Pain Rating Scale. Amitriptyline and gabapentin cost effectiveness analysis showed Average Cost-Effectiveness Ratio (ACER) are Rp 45.443,08 and Rp 52.241,52 and Incremental Cost-Effectiveness Ratio (ICER) Rp 72.636,87. Based on the results, Incremental Net Benefit (INB) showed that gabapentin is the most cost-effective than amitrityline with Rp + 59.078,37 score. Keywords: Stroke, neuropathic pain, amitriptyline, gabapentin, cost-effectiveness analysis